2008
DOI: 10.1017/s1742170507002104
|View full text |Cite
|
Sign up to set email alerts
|

Maize silage as an energy supplement in organic dairy cow rations

Abstract: The literature implicates strongly that including energy supplements in dairy rations based on protein-rich forages increases performance and feed efficiency due to an improved and more balanced ruminal energy and protein supply. Therefore, both conventional and organic dairy farms primarily supplement roughages with concentrates, containing high proportions of cereal grains. However, considering the main principles of sustainable agricultural systems and nutrient cycles, the question of alternatives is raised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
(34 reference statements)
4
2
0
Order By: Relevance
“…In an international context NDF content of maize silages were above than reported by Morgensen et al (2010) in Denmark and Velik et al (2008) in Austria, but similar to values reported by Morrison and Patterson (2007) in Northern Ireland. In terms of ADF, values for the maize silage reported herein were lower than reported by other researchers, whether from Mexico or the international context, indicating that maize silages in the present work had a good digestibility.…”
Section: Resultssupporting
confidence: 82%
“…In an international context NDF content of maize silages were above than reported by Morgensen et al (2010) in Denmark and Velik et al (2008) in Austria, but similar to values reported by Morrison and Patterson (2007) in Northern Ireland. In terms of ADF, values for the maize silage reported herein were lower than reported by other researchers, whether from Mexico or the international context, indicating that maize silages in the present work had a good digestibility.…”
Section: Resultssupporting
confidence: 82%
“…The observed feed efficiencies of 1.19–1.23 kg ECM kg −1 intake of DM lie within the range of previous reports about organically managed dairy cows, ranging from 1.11 kg milk kg −1 intake of DM when only 1.3 kg DM of concentrates were supplemented 40 (forage base consisted of grass–clover silage and maize silage) to 1.35–1.37 kg ECM kg −1 intake of DM when 10 kg DM of concentrates were supplemented 41 (forage base grass–clover silage). The gross N efficiency of 0.259 observed when feeding the ryegrass diet is similar to the level of 0.255 observed by Velik et al 42 (forage-base grass–clover silage, supplemented with 3 kg DM of concentrates), but at the lower end of the range of 0.25–0.30 that according to Chase 43 can be considered as average, while the level of 0.304 achieved with the maize diet is already slightly above average. Although the biological potential of cows to convert feed N into milk N is limited, N efficiency can be improved by reducing feed N intake and thereby optimizing the use of microbial protein synthesis in the rumen 44 .…”
Section: Discussionsupporting
confidence: 87%
“…The gross N efficiency of 0.259 observed when feeding the ryegrass diet is similar to the level of 0.255 observed by Velik et al 42 (forage-base grass-clover silage, supplemented with 3 kg DM of concentrates), but at the lower end of the range of 0.25-0.30 that according to Chase 43 can be considered as average, while the level of 0.304 achieved with the maize diet is already slightly above average. The gross N efficiency of 0.259 observed when feeding the ryegrass diet is similar to the level of 0.255 observed by Velik et al 42 (forage-base grass-clover silage, supplemented with 3 kg DM of concentrates), but at the lower end of the range of 0.25-0.30 that according to Chase 43 can be considered as average, while the level of 0.304 achieved with the maize diet is already slightly above average.…”
Section: Nutrient Balances and Efficiency Of Milk Productionsupporting
confidence: 87%
“…However, the observed IVDMD of giant miscanthus leaves and stems, and giant reed stems, would be among the lowest in a wide range of reported values (280 to 740 g•kg −1 ) for C4 grasses [25] [26]. Like many traditional livestock feeds, green-harvested tissues could be fed fresh-chopped or ensiled [11] [36]. Steer weight gain was adequate when freshchopped sugarcane was fed at 30% -40% of the total diet, but performance decreased when the dietary proportion was >60% [36].…”
Section: Digestibilitymentioning
confidence: 99%
“…Like many traditional livestock feeds, green-harvested tissues could be fed fresh-chopped or ensiled [11] [36]. Steer weight gain was adequate when freshchopped sugarcane was fed at 30% -40% of the total diet, but performance decreased when the dietary proportion was >60% [36]. This suggests that sugarcane is similar to other roughage sources (e.g.…”
Section: Digestibilitymentioning
confidence: 99%